Research on the Slurry for Long-Distance Large-Diameter Pipe Jacking in Expansive Soil. (14th October 2018) - Yang, Xian; Liu, Yang; Yang, Chao
Abstract : When the pipe jacking technology is applied in expansive formation, the soil around the pipe will easily absorb water from the slurry and expand to wrap up the pipe, producing an excessive pipe jacking force. A water-based slurry formula suitable for pipe jacking in expansive soil layer was proposed in this paper. Firstly, the key design points of pipe jacking slurry in expansive soil were put forward. Secondly, plant glue, potassium humate, Na-CMC, and graphite powder were chosen as treating agents to improve the slurry performance. The effect of addition levels of different treating agents on the funnel viscosity, filter loss, expansion ratio, friction coefficient and water dissociation rate of the slurry were tested. Thirdly, based on the results of single-factor tests, a water-based slurry formula suitable for pipe jacking in expansive soil was obtained. Finally, the slurry formula was applied in a practical pipe jacking project in expansive formation, and the jacking force was controlled well in the whole jacking process. The new water-based slurry is cheap and practical and has no pollution to environment. Furthermore, a simple and practical calculating method of the pipe jacking force was presented. The comparison of the calculated and measured pipe jacking force shows that the simple calculating method can estimate the jacking force well. Improving slurry performance to reduce jacking force in pipe jacking and predicting pipe jacking force accurately can help reducing the investment for counterforce wall and jacking system in pipe jacking engineering.